Tinjauan Hukum Pembagian Waris Anak Laki-Laki Marga Manuhor dalam Hukum Waris Adat Batak Toba - Nabilla Rahmadhani; Fanny Putri Natasya; Jihan Nurfajrina Radhwa (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Batak Toba is a tribe with strong customs in Indonesia. One of the applicable values ​​and norms is regarding the process of dividing inheritance among descendants. The existence of male descendants in Toba Batak society is very important to continue the clan. However, not all family members have male offspring. So, the tradition of buying clan (manuhor clan) emerged to overcome this. This phenomenon gives rise to differences in the distribution of inheritance for biological male descendants and male descendants of the clan. This writing provides an understanding of the legal review of the process of dividing customary inheritance for biological male descendants and sons belonging to the clan in Batak Toba. This problem will be studied using normative methods with the perspective of Toba Batak traditional inheritance law through legal studies, journals and research that has been carried out by previous researchers. This writing discusses the implementation of inheritance distribution between biological sons and sons who bear the clan in Batak Toba based on previous research analysis and community customs. The originality of this research explains the role of customary inheritance law that applies in the Toba Batak community in the process of dividing inheritance between biological sons and sons of the clan by showing the similarities and differences that occur.